Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar pada Materi KPK dan FPB di Kelas IV SDN Krueng Baung - Nurdiana Nurdiana; Patri Janson Silaban; Lasma Silaban (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Problems in learning mathematics, especially FPB and KPK material, are caused by many factors, one of which is the characteristics of mathematics. This research aims to determine student learning outcomes on KPK and FPB material in class IV of SDN Krueng Baung using the Problem Based Learning model. This research is Classroom Action Research (PTK) with a quantitative approach. The results of the research showed that there was an increase in student learning outcomes in KPK and FPB material in class IV of SDN Krueng Baung. This is proven by the results of research conducted on the pretest, 4 students (28.57%) received a passing score, while 10 students (71.42%) did not complete it, with an average score of 74.07. In the posttest, students' learning outcomes increased to 12 students (85.71%) and 2 students (14.28%) did not complete them, with an average learning outcome score of 79.21.